Diversity and Inclusion in Higher Education (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2021)
Our study clarifies the concepts of inclusion and diversity based on domestic and international studies. We examine how diversity has become a feature of higher education, and the additional causes and consequences behind the focus of inclusivity. Our questionnaire study explored the extent to which the diverse group of students of the University of Pécs (N: 809) is involved in the university social and academic life, and whether those with social disadvantages show a difference in involvement. The results revealed that socially disadvantaged students are underrepresented in large university programmes, however, student colleges and other micro- communities are more able to address these students in a personal way and to provide an inclusive environment.